Consensus of experts from the Russian Medical Society of Arterial Hypertension. Arterial hypertension and erectile dysfunction - Tatiana A. Alekseeva (IP Morozov P.V., 2021)
Sexual health is an essential part of overall health, and an active and healthy sex life is an important aspect of a good quality of life. Cardiovascular diseases and sexual health disorders have common risk factors (arterial hypertension, diabetes mellitus, dyslipidemia, obesity and smoking) and common pathogenesis (endothelial dysfunction, inflammation and atherosclerosis). All this led to speculations about the pathophysiology and treatment options for sexual dysfunctions. The use of phosphodiesterase type 5 inhibitors has revolutionized the treatment of erectile dysfunction (ED) in men. This article focuses on ED and its relationship with hypertension. This document was created by experts from the Russian Medical Society of Arterial Hypertension with the participation of a member of the European Society of Hypertension Working Group on Sexual Dysfunction and Arterial Hypertension. In recent years, the expert group was very active in educating hypertension specialists and related specialties physicians about ED via numerous lectures at national and international congresses. It has been noted that ED precedes the development of coronary heart disease. The artery diameter hypothesis has been proposed as a possible explanation for this observation. Clinical manifestations of atherosclerotic lesions and/or endothelial dysfunction of the penile arteries may precede those in larger arteries. Patients with hypertension who receive antihypertensive drugs are more likely to suffer from sexual dysfunctions compared to untreated patients. The occurrence of ED appears to be related to the undesirable effects of antihypertensive drugs on the penile tissues. There is information about various effects of antihypertensive drugs on erectile function.